Human serum inhibits adhesion and biofilm formation in Candida albicans - Ding, Xiurong (BioMed Central, 2014)
BACKGROUND: Candida albicans can form biofilms on intravenous catheters; this process plays a key role in the pathogenesis of catheter infections. This study evaluated the effect of human serum (HS) on C. albicans biofilm formation and the expression of adhesion-related genes in vitro. A C. albicans laboratory strain (ATCC90028) and three clinical strains were grown for 24 h in RPMI 1640 supplemented with HS or RPMI 1640 alone (as a control). The growth of biofilm cells of four strains was monitored by a Live Cell Movie Analyzer, and by XTT reduction assay. The expression of the adhesion-related genes BCR1, ALS1, ALS3, HWP1 and ECE1 was analyzed by RT-PCR at three time points (60 min, 90 min, and 24 h). RESULTS: In the adhesion phase, C. albicans cells kept a Brownian movement in RPMI medium containing HS until a large number of germ tubes were formed. In the control group, C. albicans cells quickly adhered to the bottom of the reaction plate. Compared with RPMI 1640, medium supplemented with 3–50% HS caused a significant decrease in biofilm development (all p < 0.001). However, the presence of HS had no significant inhibitory effect on the pre-adhered biofilms (all p > 0.05). Biofilm formation was also inhibited by heat-inactivated and proteinase K pre-treated HS. The presence of 50% HS did not significantly affect the planktonic growth of C. albicans (p > 0.05). At three time points, HS inhibited expression of the ALS1 and ALS3 genes and promoted expression of the HWP1 and ECE1 genes. Significant up-regulation of BCR1 was observed only at the 90-min point. CONCLUSIONS: Human serum reduces biofilm formation by inhibiting the adhesion of C. albicans cells. This response may be associated with the down-regulation of adhesion-related genes ALS1, ALS3 and BCR1. The inhibitory serum component is protease-resistant and heat stable.